(untitled) (Fiep Bulletin - online, 2011)
Objective: the objective of this study was to assess the knowledge level of employees of Unities of Alimentation and Nutrition situated in city of Montes Claros – MG about good practice of manipulation, hygiene and conservation. Methodology: descriptive research with quantitative character. Sample composed by 15 manipulators of feed – cooks and assisters of kitchen – from female sex. How instrument, was used a structured questionnaire with 5 general questions and 11 specifics. The data were through of descriptive statistic (percentage). The results evidenced that 60% of sample is composed by kitchen assists and 40% by cooks, in which 26.65% attended the 1st to 4th grade, 33.3% the 5th to 8th grade and 40% the 1st to 3rd year high school (complete or incomplete). The most (53.34%) did work about 1 month to 4 years and 53.34% of manipulators did participate just 1 to 2 training. As for education, those who had scholarity from 1st to 3rd year high school did agree 72.72% of proposed questions. However, those with scholarity from 1st to 4th grade presented 45.45% success. The employees who had higher time of profession (more to 12 years) did present lower number of success. In 4 questions, the rate of success was equal or inferior to 40%, 3 questions obtained 60 to 66.66% and 4 questions with 80 to 86.66% of success. Conclusion: It is concluded that the evaluated have a medium level of knowledge about good practice of manipulation, hygiene and conservation. Due to reduced number training participation in relation to time of experience in area, must be marked the importance of capacity and awareness of manipulators like strategy to get better the quality and security of offered food. So, the professional participation of nutrition is of fundamental importance to train, to follow and to assess the employees, completing in this way the current legislation.